The violations of empathy - Jennifer Cooke (2016)
This article questions the assumption that empathy is a positive, politically beneficial emotion through two examples of poetry about deaths with sensitive political dimensions. I begin by returning to the origins of ‘empathy’ in English, as written about by Vernon Lee in the earlytwentieth-century, to show how far the word has drifted from Lee’s sense of it as an embodied aesthetic response to an artwork. Rob Halpern’s book of poems Common Room refuses imaginative empathy with its subject, a dead Guantanamo Bay detainee, and yet, I show, surprisingly aligns with Lee’s sense of empathy through the author’s erotic and imaginative response to the man’s autopsy report. What results in this revivification of Lee’s empathy is a violation of the religious beliefs of the detainee. In contrast, Andrea Brady’s poem ‘Song for Florida 2’ takes up a more contemporary sense of empathy in its focus upon the killing of the unarmed teen Trayvon Martin by George Zimmerman in 2012. Brady’s poem presents several possibilities for empathising with Martin’s mother - by imagining being her, or imagining similarly losing a son - but eventually draws back from this as a limit. Empathy here risks erasing the specificity of the racialized context which led to Martin’s unjust death. The white poet’s son cannot ‘replace’, even imaginatively, the black mother’s son without effacing the difference which saw Martin targeted in the first place. Brady’s poem, I argue, marks how empathy can violate through supplanting the grief and political context for that grief of the person to whom empathy is extended. What is needed instead of empathy is a commitment to political change.